Length-Weight relationship, Condition and relative condition factor in Maydelliathelphusa masoniana and Himalayapotamon emphysetum inhabiting streams of J&K, India. - MANHAS, PRIYA; Gupta, Rakesh Kumar; LANGER, SEEMA (Innovare Journal of Life Sciences, 2018)
Presently 782 individuals of Maydelliathelphusa masoniana and 389 in Himalayapotamon emphysetum were analyzed for Weight vs CW (carapace width) relationship. The mean CW of males was recorded to be 2.3±0.52 cm CW to 6.3±0.63 cm CW and 2.2±0.32 cm CW to 5.1±0.18 cm CW whereas in females it varied from 2.2±0.14 cm CW to 5.3±0.14 cm CW and 2.1±0.13 cm CW to 4.6±0.12 cm CW in case of M. masoniana and H. emphysetum respectively. The mean weight of males recorded to be 16.4±4.2 to 142±6.3 g and 15.2±3.2 to 100.4±6.5g while in females it varied from 14.3±4.3 to 96.2±5.4g and 14.2±6.3 to 80.6±7.2g in case of M. masoniana and H. emphysetum respectively. Males of both the species were therefore, significantly heavier than females (p < 0.05). Mean condition factor (K) in M. masoniana varied from 0.0370±0.0012 to 0.066±0.0026 in males and from 0.0368±0.0032 to 0.0583±0.0025 in females whereas in H. emphysetum the condition factor varied from 0.0324±0.0028 to 0.0602±0.0022 in males and between 0.0324±0.0018 and 0.0536±0.0023 in females. The relative condition factor (Kn) in M. masoniana varied from 0.78±0.10 to 1.08±0.20 in males and from 0.64±0.12 to 0.98±0.16 in females while in H. emphysetum it varied from to 0.62±0.14 to 1.02±0.14 in males from 0.58±12 to 0.92±0.26 in females.